Work in Brazil : essays in historical and economic sociology - Adalberto Cardoso (SciELO Books - EDUERJ, 2016)
"Institutional frameworks, political action, social and political identities, class relations, social inertia and path dependence are the main aspects inquired in this book. Taken together, the chapters present a coherent and systematic portrait of Brazil, or a plausible point of view about the dynamics of our sociability which may interest the foreign reader. Collective bargaining, labour inspection, the labour and capital organizations are all elements of the Getulio Vargas legacies that, albeit with adaptations over time, still impinge upon our present. For that reason, it is impossible to understand what we are without looking back and trying and reconstruct the trajectories of the current institutions, social and political actors, and even the economy. As a consequence, most of the chapters adopt a historical sociological perspective, in dialogue between the contemporary context and the country's vivid historiography."